2018
DOI: 10.1111/dme.13698
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal, observational study examining the relationships of patient satisfaction with services and mental well‐being to their clinical course in young people with Type 1 diabetes mellitus during transition from child to adult health services

Abstract: AimWe hypothesized that participant well‐being and satisfaction with services would be positively associated with a satisfactory clinical course during transition from child to adult health care.MethodsSome 150 young people with Type 1 diabetes mellitus from five diabetes units in England were recruited to a longitudinal study of transition. Each young person was visited at home four times by a research assistant; each visit was 1 year apart. Satisfaction with services (Mind the Gap; MTG) and mental well‐being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…No significant associations between the adolescent indicators and HbA1c level were found, in line with previous studies 10–12. However, three of the seven parent indicators were correlated significantly with the adolescent HbA1c levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No significant associations between the adolescent indicators and HbA1c level were found, in line with previous studies 10–12. However, three of the seven parent indicators were correlated significantly with the adolescent HbA1c levels.…”
Section: Discussionsupporting
confidence: 90%
“…In the same study adolescents aged >13 years who reported a higher quality of care had lower HbA1c levels 9. However, other studies have not found significant correlations between the satisfaction of young peoples with diabetes care and their HbA1c levels 10–12…”
Section: Introductionmentioning
confidence: 83%
“…The prevalence of anxiety and depression is high, and mental health and well-being difficulties are up to four times higher in children with physical health LTCs than in healthy peers (Hysing et al, 2007 ; Pinquart and Shen, 2011a , b ; Ferro, 2016 ; Brady et al, 2017 ). Mental health is a key predictor of a successful clinical course; for example, baseline depression in children with rheumatic diseases was associated with higher levels of pain and disability 4 years later (Colver et al, 2018 ; Gray et al, 2018 ; Hanns et al, 2018 ). Good childhood mental health optimizes engagement in daily activities for children and families; facilitates psychosocial development, educational attainment, and increased life-course opportunity; and protects against adult mental health problems (DoH, 2011 ; Colver et al, 2018 ; Tollisen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial issues are common in this phase, and young T1DM patients have signi cantly higher rates of diabetes-related distress than other age groups [7]. These issues could lead to deterioration of glycosylated hemoglobin (HbA1c) levels with an associated increase in acute and even chronic complications such as ketoacidosis or microvascular problems [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It is not feasible to implement all interventions at every center, and generalizability is often limited due to differing study designs and outcome measures [6,19]. As a result, factors that effectively in uence the transition process are still poorly understood [11,[20][21][22][23][24]. Consensus on the de nition of transition success is lacking, and little high-quality evidence on which to base transition practice is available [6,19].…”
Section: Introductionmentioning
confidence: 99%